2023
DOI: 10.3390/ijms241310539
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 Gene and ABCG2 Protein Expression in Colorectal Cancer—In Silico and Wet Analysis

Aleksandra Sałagacka-Kubiak,
Dawid Zawada,
Lias Saed
et al.

Abstract: ABCG2 (ATP-binding cassette superfamily G member 2) is a cell membrane pump encoded by the ABCG2 gene. ABCG2 can protect cells against compounds initiating and/or intensifying neoplasia and is considered a marker of stem cells responsible for cancer growth, drug resistance and recurrence. Expression of the ABCG2 gene or its protein has been shown to be a negative prognostic factor in various malignancies. However, its prognostic significance in colorectal cancer remains unclear. Using publicly available data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…SLC4A4 and SLC9A3 can transport H + and HCO 3 – , respectively, thus affecting tumor cell PH regulation. SLC15A1 has a significant effect on intestinal peptide transport affects intestinal diseases. , SLC38A3 is known for its involvement in amino acid transport and is extensively documented in neurological disorders. Previous studies have explored the role of SLC38A3 in glutamine metabolism and its effect on tumor progression. Our study identified SLC38A3 as a novel prognostic marker gene in CRC, and the knockdown of SLC38A3 in HCT cells inhibited CRC cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLC4A4 and SLC9A3 can transport H + and HCO 3 – , respectively, thus affecting tumor cell PH regulation. SLC15A1 has a significant effect on intestinal peptide transport affects intestinal diseases. , SLC38A3 is known for its involvement in amino acid transport and is extensively documented in neurological disorders. Previous studies have explored the role of SLC38A3 in glutamine metabolism and its effect on tumor progression. Our study identified SLC38A3 as a novel prognostic marker gene in CRC, and the knockdown of SLC38A3 in HCT cells inhibited CRC cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…SLC15A1 has a significant effect on intestinal peptide transport affects intestinal diseases. 19 , 22 24 SLC38A3 is known for its involvement in amino acid transport and is extensively documented in neurological disorders. 25 27 Previous studies have explored the role of SLC38A3 in glutamine metabolism and its effect on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies definitely helped us to guide the construction of our study tenets and we are most grateful to their authors for their guidance and direction. Naturally, as technology advances, other biomarkers will come to the fore and we mention some for our readers' interest in References [48,49]. In a relatively recent comprehensive review [50] of IHC staining methods, Adnab-9 was one of 8 other markers selected (p53, β-catenin, COX2, Ki-67, Cyclin D1, Annexin A10, Aldehyde Dehydrogenase Isoform 1A1).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the ABCG2 gene has demonstrated negative prognostic implications in various malignancies, while in CRC, its prognostic significance remains undefined [25][26][27]. By analyzing publicly available datasets, Sałagacka-Kubiak et al demonstrated that ABCG2 is downregulated in colon and rectum adenocarcinomas, exhibiting lower expression levels compared to both adjacent non-malignant tissues [28]. This deregulation is suggested to be associated with the methylation level of specific sites within the ABCG2 gene and correlated with microsatellite instability (MSI), weight, and age, whilst in rectum adenocarcinoma patients, it was linked to tumor localization, population type, and age.…”
mentioning
confidence: 99%